The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11121-013-0449-8
|View full text |Cite
|
Sign up to set email alerts
|

School Victimization and Substance Use among Adolescents in California

Abstract: Substance use and violence co-occur among adolescents. However, the extant literature focuses on the substance use behaviors of perpetrators of violence and not on victims. This study identifies patterns of school victimization and substance use and how they co-occur. The California Healthy Kids Survey was used to identify latent classes/clusters of school victimization patterns and lifetime and frequency of recent (past month) alcohol, tobacco, and marijuana use (N =419,698). Demographic characteristics (age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 46 publications
(57 reference statements)
2
24
1
2
Order By: Relevance
“…We found that Hispanic and Asian youth were less likely to be concurrent users of some typologies than White adolescents (A+C and A+M+C) and null effects for the other typologies (A+M, M+C). These findings contradict previous research suggesting that Hispanic youth are at higher risk for concurrent use than their White peers (Connell et al, 2009; Gilreath et al, 2014; Gilreath et al, 2015), as well as research suggesting Asian youth are at lower risk for A+M and M+C than Whites and other racial/ethnic groups (Lanza et al, 2010; Ramo et al, 2012). Native American youth were found not to differ from Whites on use of any concurrent substance-use typology.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We found that Hispanic and Asian youth were less likely to be concurrent users of some typologies than White adolescents (A+C and A+M+C) and null effects for the other typologies (A+M, M+C). These findings contradict previous research suggesting that Hispanic youth are at higher risk for concurrent use than their White peers (Connell et al, 2009; Gilreath et al, 2014; Gilreath et al, 2015), as well as research suggesting Asian youth are at lower risk for A+M and M+C than Whites and other racial/ethnic groups (Lanza et al, 2010; Ramo et al, 2012). Native American youth were found not to differ from Whites on use of any concurrent substance-use typology.…”
Section: Discussioncontrasting
confidence: 99%
“…In general, male adolescents report higher rates of daily alcohol, marijuana, and cigarette use than female adolescents (Lanza et al, 2015; Miech et al, 2016). As for concurrent use, the most consistent sex effect has been found for occasional concurrent users (i.e., lifetime users of alcohol, marijuana and cigarettes, with little recent concurrent use), who are more likely to be female than male (Connell et al, 2010; Gilreath et al, 2014; Gilreath et al, 2015). However, findings have been mixed regarding sex differences in the frequent/recent use of alcohol, marijuana and cigarettes.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Participants respond on a 5 point scale ranging from strongly disagree to strongly agree. The CHKS has excellent psychometric properties (Gilreath, Astor, Estrada, Johnson, Benbenishty, & Unger, 2014;Sharkey, You, & Schnoebelen, 2008).…”
Section: Instrumentationmentioning
confidence: 99%